Project-Based Learning (PjBL) Integrated with STREAM-ESD in Kombucha Tea Production to Enhance Students’ Critical Thinking Skills - Abdilah, Ajeng Nadia Utami; Tri wahyu Agustina; Yulia Sukmawardhani (Universitas Negeri Semarang, 2025)
This study aims to examine the effectiveness of STREAM-integrated Project-Based Learning This study investigates the effectiveness of a Project-Based Learning (PjBL) model integrated with the STREAM–ESD (Science, Technology, Religion, Engineering, Arts, Mathematics – Education for Sustainable Development) approach in enhancing junior high school students’ critical thinking skills within the topic of biotechnology. Utilizing a quasi-experimental design, the research was conducted on Grade IX students in South Cianjur, West Java, through a kombucha tea production project grounded in real-world application and interdisciplinary inquiry. The intervention involved four stages: problem definition, data collection, building, and utilization. Results from pretest and posttest assessments revealed a significant increase in critical thinking skills in the experimental group (N-Gain = 0.7057, high category) compared to the control group (N-Gain = 0.4514, moderate category), with statistical tests confirming a meaningful difference (p < 0.05). The findings demonstrate that the integration of STREAM and ESD into PjBL fosters analytical thinking, creativity, and moral reasoning through contextual learning experiences. Moreover, the inclusion of ethical and religious perspectives encouraged students to consider the social and spiritual implications of scientific practices. This research contributes to the ongoing discourse on educational innovation by offering a sustainable, student-centered, and culturally responsive model for science education aligned with the goals of Indonesia Emas 2045 and the UN Sustainable Development Goals